2000
DOI: 10.1073/pnas.97.1.309
|View full text |Cite|
|
Sign up to set email alerts
|

The IgG Fc receptor, FcγRIIB, is a target for deregulation by chromosomal translocation in malignant lymphoma

Abstract: Rearrangement of chromosomal bands 1q21–23 is one of the most frequent chromosomal aberrations observed in hematological malignancy. The genes affected by these rearrangements remain poorly characterized. Typically, 1q21–23 rearrangements arise during tumor evolution and accompany disease-specific chromosomal rearrangements such as t(14;18) ( BCL2 ) and t(8;14) ( MYC ), where they are thus thought to play an important role in tumor progression. The pathogenetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 57 publications
7
51
1
Order By: Relevance
“…Rearrangement of chromosomal band 1q21-23 is one of the most common secondary alternations associated with B-cell NHL [16,17], yet only six have been characterized to date. Three of these were shown by Callanan et al [18] to deregulate the IgGFc receptor, FcgRllB. We have shown by Southern blotting, using a probe (EC2) specific for the FCGR2 genes [18], that this locus is also altered in the patient described here.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Rearrangement of chromosomal band 1q21-23 is one of the most common secondary alternations associated with B-cell NHL [16,17], yet only six have been characterized to date. Three of these were shown by Callanan et al [18] to deregulate the IgGFc receptor, FcgRllB. We have shown by Southern blotting, using a probe (EC2) specific for the FCGR2 genes [18], that this locus is also altered in the patient described here.…”
Section: Discussionsupporting
confidence: 57%
“…Three of these were shown by Callanan et al [18] to deregulate the IgGFc receptor, FcgRllB. We have shown by Southern blotting, using a probe (EC2) specific for the FCGR2 genes [18], that this locus is also altered in the patient described here. This finding adds support to the possibility that deregulation of this gene can be related to the development of lymphoma/leukemia.…”
Section: Discussionsupporting
confidence: 57%
“…They establish a dense SNP map which will facilitate the discovery of genetic variations underlying susceptibility to autoimmune and other diseases. They indicate that the chromosome 1q breakpoint, seen for certain lymphomas, 41 may lie just telomeric to Fc␥RIIIB in the low affinity Fc␥R cluster. This observation suggests a possible recombination hot spot, given the occurrence of both Fc␥RIIIB gene deletion and duplication in humans.…”
Section: Discussionmentioning
confidence: 99%
“…110,111 Moreover, the FCGR2B gene (FcgR-IIB) also at 1q21 has been found in IgL translocations secondary to t(14;18), as well as in IgH translocations, in a small number of FLs. 112,113 Deletions at 6q11-27 are frequently found in FL and are associated with an adverse prognosis. [105][106][107] In two studies on the 6q11-27 deletions, a region of minimal deletion was identified at 6q16.3, harboring the SIM1, RNAH, DJ and GRIK genes.…”
Section: Secondary Gene Alterations In Flmentioning
confidence: 99%